2014
DOI: 10.1055/s-0034-1383367
|View full text |Cite
|
Sign up to set email alerts
|

Der Effekt der pseudophaken Minimonovision als Option einer Brillenunabhängigkeit im Alltag

Abstract: Das menschliche Auge eines Erwachsenen ist nahezu kugelförmig, misst im Durchmesser etwa 24 mm und wiegt etwa 7,5 g. Die Wand des Augapfels besteht außen aus der weißen, bindegewebigen Lederhaut (Sklera), die dem Augapfel die Form gibt und von der Bindehaut bedeckt wird, und der klaren Hornhaut (Kornea). Letztere weist eine stärkere Krümmung auf. g max = g + gw g min = g -gn Da die Gegenstandsweite mit der Lage des Fernpunktes gleichgesetzt wird, muss für jede Gegenstandsentfernung eine entsprechende Brennwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…This high level of patient satisfaction is in agreement with the outcome reported in other studies evaluating the results of pseudophakic micro-monovision with monofocal IOLs. 10 , 11 , 15 Zettl et al 10 found a high patient satisfaction score of 93.18 in the VF-14 questionnaire after the implantation of monofocal IOLs generating an anisometropia between 0.5 and 1.75 D. Likewise, the level of patient satisfaction achieved in our study with the ERV IOL and a monovision of around 0.75 D is also consistent with that reported for different multifocal IOLs. 7 , 16 , 17 , 19 Mendicute et al 16 found that more than 90% of patients implanted with a trifocal diffractive IOL were satisfied with the visual outcome.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This high level of patient satisfaction is in agreement with the outcome reported in other studies evaluating the results of pseudophakic micro-monovision with monofocal IOLs. 10 , 11 , 15 Zettl et al 10 found a high patient satisfaction score of 93.18 in the VF-14 questionnaire after the implantation of monofocal IOLs generating an anisometropia between 0.5 and 1.75 D. Likewise, the level of patient satisfaction achieved in our study with the ERV IOL and a monovision of around 0.75 D is also consistent with that reported for different multifocal IOLs. 7 , 16 , 17 , 19 Mendicute et al 16 found that more than 90% of patients implanted with a trifocal diffractive IOL were satisfied with the visual outcome.…”
Section: Discussionsupporting
confidence: 90%
“…This option also provided high levels of spectacle independence at near (75.0% in group 4, 74.1% in group 5), which was better than spectacle independence levels reported for mini-monovision approaches with monofocal IOLs. 10 , 11 , 13 , 15 Likewise, this level of spectacle independence was equivalent to that found with some multifocal IOLs. 16 , 17 …”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations